Environmental, social, and governance and corporate efficiency: Mediating role of R&D in achieving sustainable development goals - Kweh, Qian Long; Ting, Irene Wei Kiong; Ren, Chunya; Lu, Wen-Min (Taylor & Francis Online, 2023)
We examine whether and how research and development (R&D) mediates the association between environmental, social, and governance (ESG) pillars and corporate efficiency among companies within the supply chain of Microsoft Corporation from 2012 to 2020. An estimation of corporate efficiency using data envelopment analysis (DEA) indicates that companies should first improve their innovational efficiency (mean DEA score = 0.371), then operational efficiency (mean DEA score = 0.659), and finally profitability efficiency (mean DEA score = 0.695). Moreover, a mediation analysis confirms the mediating role of R&D intensity. Overall, R&D should be one of the spotlights in the supply chain amidst the highlights on ESG in this dynamic and challenging business world for companies to achieve sustainable development goals.